Interference of Climate Change on Plant-Microbe Interaction: Present and Future Prospects - Sharma, Binny; Singh, Bansh Narayan; Dwivedi, Padmanabh; Rajawat, Mahendra Vikram Singh (Frontiers in Agronomy, 2022)
Plant mutualistic association with various beneficial microbes is referred to as the microbiome. These microbes are found either in episphere or endosphere of the plant tissues. Several pieces of evidence have highlighted that plant microbiomes and soil play a pivotal role in making soil nutrient balance which is readily available to plants and provide strength under various stresses. Recently different technologies relevant to plant microbiome and diversity such as sequencing technologies, metagenomics and bioinformatics have been utilized. Knowledge about factors that shape the composition of plant microbes is still less explored. Here, current insights into the issues driving the above/below plant microbial diversities are explored. Primarily, we address the distribution of microbial communities above and below ground across plant habitats that have benefitted plants. Finally, we summarize factors that promote the structure and composition of the plant microbiome.